Types of the New World Stigmoderini (Coleoptera: Buprestidae) deposited in Finnish Museum of Natural History, Helsinki (Buprestidae: Buprestinae: Stigmoderini) - Pineda, Cristian (Zootaxa, 2022)
Illustrations are provided for the six type specimens of New World Stigmoderini deposited in the Finnish Museum of Natural History, Helsinki. Comments and current status are provided for each species.